2014
DOI: 10.1016/j.addr.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Stable RNA nanoparticles as potential new generation drugs for cancer therapy

Abstract: Human genome sequencing revealed that only ~1.5% of the DNA sequence coded for proteins. More and more evidence has uncovered that a substantial part of the 98.5% so-called “junk” DNAs actually code for noncoding RNAs. Two milestones, chemical drugs and protein drugs, have already appeared in the history of drug development, and it is expected that the third milestone in drug development will be RNA drugs or drugs that target RNA. This review focuses on the development of RNA therapeutics for potential cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
188
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(189 citation statements)
references
References 211 publications
1
188
0
Order By: Relevance
“…Moreover, nanostructures of different shapes and sizes have been proposed as an effective delivery system for siRNA, ribozymes, etc. [106,107]. Recently, it has been demonstrated that branched small RNA structures may also be effective RNAi inducers.…”
Section: Long-interfering Rnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, nanostructures of different shapes and sizes have been proposed as an effective delivery system for siRNA, ribozymes, etc. [106,107]. Recently, it has been demonstrated that branched small RNA structures may also be effective RNAi inducers.…”
Section: Long-interfering Rnasmentioning
confidence: 99%
“…Initially, branched oligonucleotides were applied to study mRNA splicing [102][103][104]. Then diverse branched structures were used as building blocks for self-assembling nanostructures [105][106][107]. Moreover, nanostructures of different shapes and sizes have been proposed as an effective delivery system for siRNA, ribozymes, etc.…”
Section: Long-interfering Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The main types of nanoparticles used for conveying siRNA and miRNA are cationic liposomes or positively charged polymers, such as polyethylenimine, or waterinsoluble polymers, such as poly-lactide-co-glycolide. 79 For example, in a diethylnitrosamine-induced HCC mouse model, systemic administration of miR-124 through liposomes led to a reduction in tumor growth and tumor size via induction of apoptosis and deregulation of an miRNA/inflammatory feedback loop circuit involving hepatocyte nuclear factor 4 alpha 80 (see Table 5 for a list of nanocarrier formulations used in miRNA delivery). Trang et al have used neutral lipid emulsions to mediate the delivery of miR-let-7 and miR-34a in a non-small cell lung cancer model.…”
Section: Nanotechnologies For In Vivo Delivery Of Mirnasmentioning
confidence: 99%
“…RNA-containing drugs can accelerate tissue regeneration upon damage, change the course of the inflammatory process, stimulate subpopulations of lymphocytes, enhance phagocytosis of macrophages and influence the body's responses to tumors and allografts (Afjeh et al, 2013;Dogini et al, 2014;Shu et al, 2014;Zeliadt, 2014). These effects of RNA-containing substances can be useful in correcting of age-associated conditions (Ni et al, 2011;Masuda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%